Seed yield of sunflower (Helianthus annuus L.) in rice fallow system: Seed yield of sunflower (Helianthus annuus L.) in rice fallow system - D LAKSHMI KALYANI; K PRABAHKAR; K VENKATA RAMANAMMA; S NEELIMA (Journal of Oilseeds Research, 2020)
A field study was conducted during 2017-18 in rabi season in kharif paddy fallow to study the effect of varying tillage practices, fertilizer levels and hybrids on sunflower yield. Higher seed yield (1005 kg/ha) was recorded with zero tillage, which was comparable with minimum tillage (858 kg/ha). Lower seed yield was recorded with reduced tillage (707 kg/ha), which was on par with conventional tillage (711 kg/ha). Sunflower crop responded up to 150% RDF (904 kg/ha) and harvested greater seed yield than 100% RDF (815 kg/ha) and 50% RDF (736 kg/ha). Seed yield of KBSH-44 and NDSH-1012 were on par with each other and significantly greater than DRSH-1.